Proximity induced superconductivity in bulk Cu-Nb composites: The influence of interface's structural quality - Stamopoulos, D.; Pissas, M.; Sandim, M.J.R.; Sandim, H.R.Z. (PHYSICA C-SUPERCONDUCTIVITY AND ITS APPLICATIONS, 2006)
The influence of the structural quality of a normal metal-superconductor interface on the strength of the proximity effect is studied for the cylindrical geometry of bulk Cu-Nb multifilamentary composite samples. In as-drawn Cu-Nb samples the superconducting properties induced to the Cu matrix due to its proximity with Nb filaments are manifested in the magnetization measurements through a pronounced peak positioned in the low-field regime. By systematic annealing in an extended temperature regime for various durations we changed the structural quality of the Cu-Nb interfaces and as a result their transparency to the superconducting carrier. The direct comparison of scanning electron microscopy images with magnetization data revealed that the distortion of the Cu-Nb interfaces is responsible for the suppression of the proximity effect. (c) 2006 Elsevier B.V. All rights reserved.